Veganic Agriculture in the United States: Opportunities for Research, Outreach, and Education - Alisha Utter; Mona Seymour ([TEST] Journal of Extension, 2021)
A growing number of farmers are excluding animal inputs from crop production, an approach commonly referred to as veganic or stockfree organic agriculture. This research-based article discusses the soil health and fertility strategies reported by a sample of U.S. veganic farmers. These approaches may be relevant beyond the veganic community to farmers seeking innovative methods for produce safety and nutrient cycling. Agricultural outreach professionals (AOPs), including Extension personnel, play a critical role in supporting veganic practices by serving as cross-pollinators between farmers and research institutions. Thus, the article endeavors to expand AOP familiarity with veganic practices and benefits.
Keywords: veganic; stockfree organic; alternative agriculture; plant-based; green manures